2018
DOI: 10.1016/s2214-109x(18)30283-3
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, mortality, and long-term consequences associated with diarrhoea from Cryptosporidium infection in children younger than 5 years: a meta-analyses study

Abstract: SummaryBackgroundThe protozoan Cryptosporidium is a leading cause of diarrhoea morbidity and mortality in children younger than 5 years. However, the true global burden of Cryptosporidium infection in children younger than 5 years might have been underestimated in previous quantifications because it only took account of the acute effects of diarrhoea. We aimed to demonstrate whether there is a causal relation between Cryptosporidium and childhood growth and, if so, to quantify the associated additional burden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
281
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(292 citation statements)
references
References 43 publications
4
281
2
5
Order By: Relevance
“…Burden of disease studies, focussed on acute illness, estimate 4.2 million disability adjusted life years lost in children under 5 years [64], with longer term sequelae, including growth faltering and cognitive defects. Disease impact studies in high-income countries found longer term impacts following acute infection involving persistent abdominal pain, myalgia/arthralgia and fatigue [78], irritable bowel syndrome [79], and a recent study has shown a strong association between Cryptosporidium infection and human colon cancer [80].…”
Section: Box 1 Impact Of Cryptosporidiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Burden of disease studies, focussed on acute illness, estimate 4.2 million disability adjusted life years lost in children under 5 years [64], with longer term sequelae, including growth faltering and cognitive defects. Disease impact studies in high-income countries found longer term impacts following acute infection involving persistent abdominal pain, myalgia/arthralgia and fatigue [78], irritable bowel syndrome [79], and a recent study has shown a strong association between Cryptosporidium infection and human colon cancer [80].…”
Section: Box 1 Impact Of Cryptosporidiosismentioning
confidence: 99%
“…The impact of the disease is far reaching and recent studies have highlighted the longterm consequences of clinical disease in both humans and livestock animals (Box 1). The true burden of disease in both public [64] and veterinary health is unknown, as many incidences of infection and disease go undiagnosed or unreported. With livestock farming moving towards increasingly efficient and sustainable production to minimise impact on the environment, there is much to be gained from tackling cryptosporidiosis.…”
Section: A One Health Approachmentioning
confidence: 99%
“…Cryptosporidium is a leading cause of moderate-to-severe diarrhea in children under two years old and the leading pathogen associated with death in toddlers (ages 12 to 23 months 1 ). Nitazoxanide is only one FDA approved medicine available for cryptosporidiosis, but it has limited efficacy in the population at the highest risk for poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…(36) The majority of human infections are caused by the C. hominis, C. meleagridis, and C. parvum species, members of the phylum Apicomplexa. (5, 7, 8) As cryptosporidiosis is transmitted fecal-orally, contact with any reservoir with possible fecal contamination could serve as point of transmission. In the developed world, cryptosporidia are an important cause of diarrhea in individuals living with HIV and is the most common pathogen causing waterborne outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…In the developed world, cryptosporidia are an important cause of diarrhea in individuals living with HIV and is the most common pathogen causing waterborne outbreaks. (8)…”
Section: Introductionmentioning
confidence: 99%